Music, neurology, and neuroscience: historical connections and perspectives - Altenmüller, Eckart (Progress in brain research, 2015)
"Music, neurology, and neuroscience : historical connections and perspectives provides a broad and comprehensive discussion of history and new discoveries regarding music and the brain, presenting a multidisciplinary overview on music processing, its effects on brain plasticity, and the healing power of music in neurological and psychiatric disorders. In this context, the disorders that plagued famous musicians and how they affected both performance and composition are critically discussed, as is music as medicine and its potential health hazard. Additional topics, including the way music fits into early conceptions of localization of function in the brain, its cultural roots in evolution, and its important roles in societies and educational systems are also explored. Examines music and the brain both historically and in the light of the latest research findings. The largest and most comprehensive volume on "music and neurology" ever written. Written by a unique group of real world experts representing a variety of fields, ranging from history of science and medicine, to neurology and musicology. Includes a discussion of the way music has cultural roots in evolution and its important role in societies."--[Source inconnue]
Literaturangaben
Keywords: Aufsatzsammlung; Geschichte; Neurologie; Musik